2022
DOI: 10.3389/fpls.2022.1007276
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure dose-dependently affects oxidative stress, AsA-GSH, photosynthesis, and mineral content in pakchoi (Brassica chinensis L.)

Abstract: Lead (Pb) is a heavy metal pollutant and negatively affects agriculture and ecosystems. Pb can cause oxidative stress and abnormal plant growth. The ascorbic acid-glutathione (AsA-GSH) cycle mainly exists in chloroplasts and resists oxidative stress, scavenges reactive oxygen radicals, and maintains normal photosynthesis. However, the dosage related effects of Pb on pakchoi photosynthesis, via oxidative stress and the AsA-GSH system, remains unclear. In this study, various Pb dosage stress models were tested (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Then, the GSH content was measured with the DTNB method in sample extractions before and after adding GR, respectively. The GSSG content was calculated from the difference between two measurements [31,32]. The DHA content was determined by using the commercial kit BC1240 (Solarbio Life Science, Beijing, China).…”
Section: Evaluation Of Celllular Redox Statusmentioning
confidence: 99%
“…Then, the GSH content was measured with the DTNB method in sample extractions before and after adding GR, respectively. The GSSG content was calculated from the difference between two measurements [31,32]. The DHA content was determined by using the commercial kit BC1240 (Solarbio Life Science, Beijing, China).…”
Section: Evaluation Of Celllular Redox Statusmentioning
confidence: 99%
“…When plants are exposed to Pb stress, the development of roots and aerial parts is attenuated, especially in roots, probably due to increased Pb accumulation [18,19]. Previous studies have shown that the reasons for the retardation of seed germination and plant growth under Pb are as follows: inhibited enzyme activity [20], disruption of plant water status [21], disruption of nutrient uptake [22], photosynthesis inhibition [23], disruption of cell division [24], oxidative stress [25], and lipid peroxidation [26]. To survive in soils, plants adopt several mechanisms to mitigate Pb stress, including cell wall adsorption and obstruction [27], excretion of metal ions into extracellular spaces [28], cellular sequestration [28], an increase in nonenzymatic antioxidants [29], and an increase in metalbinding ligands [30].…”
Section: Introductionmentioning
confidence: 99%